Polarização política e o impeachment de 2016: uma análise de dados reais e de mídias sociais - Roberta Coeli Neves Moreira (2019)
Political events are often topics of heated discussions around the globe, which tend to increase the opinion divergences among individuals. The emergence of these contrasting ideas deﬁnes the political polarization, a phenomenon which have been evidenced and boosted by the popularization of Internet access and social networks over the last few years. In Brazil, the political polarization was intensiﬁed by the impeachment of Dilma Rousseﬀ and its related events, revealing ideological conﬂicts among the citizens and the political elites not only in the streets but also in online social media. In view of the growing inﬂuence of the social platforms in the opinion formation of people, our work aimed at developing computational methods to analyze real-world and socialmedia data in order to study political polarization, with a focus on the impeachment proceedings of 2016 in Brazil. Our methodology involved 4 main parts: I) the temporal topic evolution from the tweets posted by Brazilian representatives; II) the measurement of the polarities and the overall polarization of the Brazilian general public in Twitter and of the representatives in their votes on bills at the Lower House; III) the correlations between the polarization of the politicians and their discussed topics on Twitter; and IV) an analysis of the associations between the politicians and the general public polarization. Our results showed that the political crisis and the activities of the representatives were the most relevant topics discussed by the politicians on Twitter. Regarding the polarization analysis, we observed that the politicians polarization increased after December of 2015, coinciding with the launch of the impeachment proceedings at the Lower House. The general public presented high values of polarization duringthewholeperiod, recordinghighervalueswhencomparedtotherepresentatives. By analysing the variables related to the polarization metric, we also observed that the polarization among politicians was more aﬀected by the level of divergence between the central opinions of the main opposite groups. On the other hand, small ﬂuctuations in the people polarization are related to diﬀerences in the size of the contrary groups, meaning that the polarization phenomenon among Brazilian citizens is more inﬂuenced by the number of individuals which join any of the ideologically opposed groups.